From Selfhood to Social Solidarity; From a Mind towards the Collective Thinking and Working Bodies: A Marxist Approach - Jose Mario De Vega (Scientia, 2022)
What our minds and conceive, our bodies can achieve. I will argue that “the mind is not then an autonomous substance, capable of forming its own states without recourse to what lies beyond it: it states arrive by courtesy of a specific external environment.” It means that, our minds appropriates the contents of the material world and this act in turn forms the other contents of our minds and its various categories. Hence, it is not a “surprising thesis that the very constitution of mind is logically bound up with environment. The geography of the mind depends upon actual geography. Undeniably the content of our minds is influenced by society and the world in general, for the former arises because of the existence of the latter.